Eficácia preclusiva da coisa julgada - Sá, Renato Montans de (2010)
The judicial estoppel exercises an undeniable safety function in the legal relationships submitted to the Judiciary. The mandatory, as an essential characteristic of the jurisdiction, can only be completely in force if what has not been decided cannot be either invalidated or reduced by a later decision. However, this protection provided by the State is circumscribed by limits set by the law. The protection granted by the res iudicata cannot be bigger than the res iudicanda. Its limits are contained within the dispute itself. In spite of the fact of the dispute being polysemy, it being possible to confuse it with the process itself, it constitutes, to the end proposed by this paper, the conflict of interests (or part of it) projected to the process. The doctrine does not conflict by assessing that the judicial estoppel is an institution of an eminently practical nature: immunization of the decision submitted to the jurisdiction. In this way, only the part that modifies the reality of the subjects of the process interests to the stability of the judicial estoppel, meaning, the dispositive. Our ordinance does not create this same protection for the logical iter that took the judger to reach his conclusions. In spite of it being important and essential for the understanding of what has been decided, the fundaments are not reached by the res iudicata. The fundaments have a close relationship with the causa petendi formulated by the author and the causa excipiendi presented by the defendant as if an imaginary shaft that connected the two ends, as assessed by the authorized doctrine. The system would be reduced to an almost inexistent safety if new arguments that modified the causa could be drawn in a new demand since they had not been drawn in the first one. The present paper has as its objective to face what material of the first process becomes unchangeable or irrelevant (according to the doctrine) for further discussions. In this way, the study of the preclusive coming into force of the judicial estoppel has in the theory of a triple identity, in its entire analysis, the essential structure for the understanding of the institution